ENGLISH LITERATURE TEACHING: AN INDONESIAN CONTEXT - Novianti, Nita (Indonesian Journal of Applied Linguistics, 2016)
Literature has gained an increasingly important place in language learning. Particularly in the EFL context, it has been regarded as beneficial for the improvement of English skills. However, there is not much attention given to the teaching of English literature for the sake of literature, not merely as a tool or technique in language learning, especially in Indonesia. The research therefore aims to investigate the teaching of English literature to EFL students in Indonesian universities. More specifically, it attempts to find how English literature lecturers select literary texts, what problems encountered by lecturers in teaching English literature to EFL students, and how they cope with the problems. A case study to three lecturers teaching three different literature courses in a state university in Indonesia was conducted. The findings show that: First, lengths, levels of language difficulty, canonical status, and the cultural background of the author become the main consideration for selecting the literary texts to teach; Second, the problems encountered are of threefold, namelyÂ reading habit, English proficiency, and resources; and Third, some of the strategies to cope with the problems consist of individual reading assignment, reading group, and taking the most advantage of the internet for teaching resources. This research has demonstrated that there are many areas for further studies in the teaching of English literature to EFL students in Indonesia, finding effective teaching models is one of them.